The Effect Of Chicken Manure Doses On The Growth And Production Of Land Kale Plants (Ipomoea Reptans.Poir) (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
The objective of this research was to determine the effect of the optimum dose of chicken manure on the growth and production of land kale plants. The research was conducted from July to August 2023 in Talimoro Village, Ermera sub-District, Ermera Municipality, at an altitude of 800 m. above the sea level. The experimental design used was a single factor Randomized Block Design (RBD), with 4 treatments repeated 4 times in 4 blocks, the dose of chicken manure with the symbol (A) and the dose/plant was as follows: A0 = No dose of chicken manure (Control) or 0 gr/plant; A1= Dosage of chicken manure 100g/plant; A2 = Dosage of chicken manure 200 g / plant; and A3 = chicken manure dose of 300 gr/plant. Thus, the total plots obtained 16 plot units.The results of the research showed that treatment with a dose of chicken manure of 200 gr/plant provided the best growth in all parameters observed, namely, number of leaves, plant height, stem diameter and leaf area and also the highest production yield, namely 4.51 Kg/plot or 23.00 tons. /ha, and the lowest production results were obtained in the treatment without a dose of manure (Control), namely 1.31 Kg/plot or 6.68 tons/ha and the optimum results were obtained in the treatment with a dose of 100 gr/plant chicken manure with a value of 2.86 kg/plot or 12.55 tons/ha.